2010
DOI: 10.1192/pb.bp.108.021212
|View full text |Cite
|
Sign up to set email alerts
|

Improving physical health monitoring for out-patients on antipsychotic medication

Abstract: Aims and methodMental illness is associated with increased physical morbidity. We aimed to assess and improve the routine blood testing of prescribed antipsychotics in out-patients from a busy London inner city area. Audit findings were presented locally to prescribers, together with educational suggestions to improve physical health assessment.ResultsInitially, the numbers monitored were low in the overall number of 126 patients included in the first audit. Following the intervention, this improved significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The present study found that a relatively small proportion (24%) of case-managed consumers with SMI received full CMM during the audit period, despite a high proportion of the study population prescribed second-generation antipsychotics. The CMM rates for weight (61%), blood pressure (38%), hyperglycaemia (59%), and dyslipidaemia (49%) are in keeping with findings from previous research, although most previous studies have used a 12-month audit period (Barnes et al 2008;Gonzalez et al 2010;Organ et al 2010). The present study identified that blood pressure was the least-recorded cardiometabolic risk test undertaken, despite the availability of sphygmomanometers and the non-invasive nature of the test.…”
Section: Rates Of Cmmsupporting
confidence: 86%
“…The present study found that a relatively small proportion (24%) of case-managed consumers with SMI received full CMM during the audit period, despite a high proportion of the study population prescribed second-generation antipsychotics. The CMM rates for weight (61%), blood pressure (38%), hyperglycaemia (59%), and dyslipidaemia (49%) are in keeping with findings from previous research, although most previous studies have used a 12-month audit period (Barnes et al 2008;Gonzalez et al 2010;Organ et al 2010). The present study identified that blood pressure was the least-recorded cardiometabolic risk test undertaken, despite the availability of sphygmomanometers and the non-invasive nature of the test.…”
Section: Rates Of Cmmsupporting
confidence: 86%
“… 28 34–37 39 MS monitoring was evaluated using the following measurements: BP, smoking status, waist circumference (WC), fasting blood glucose (BG), BMI, triglycerides and HDL-C. These measures were based on the following clinical guidelines: National Institute for health and Care Excellence 26 31 35–37 39–41 ; Maudsley Prescribing Guidelines 34 37 40–42 ; US Preventive Services Task Force 30 44 ; National Heart, Lung and Blood Institute 33 ; American Diabetes Association 32–34 38 47 ; Early Psychosis Prevention and Intervention Centre 43 ; Psychotropic Therapeutic Guidelines 48 and the American Psychiatric Association Practice. 28 35 38 Most interventions were multifaceted, so will appear in more than one cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies 28 32–34 36–39 evaluated the effectiveness of using a screening tool to increase uptake and raise staff awareness of physical health screening. Barriers to successful intervention implementation included ‘social desirability bias’ 28 36 (patients self-report their health behaviour in an overly positive picture in an effort to please their key workers); low uptake of physical measurements (eg, WC, 32 37 BP, 38 fasting BG 33 37 ) and of data on sensitive topics 36 ; difficulty to capture monitoring results onto the tool 28 32 38 39 ; difficulty in obtaining equipment 37 38 and accessing laboratory services 33 ; lack of integration with primary care for treatment or referral 33 37 38 ; appointment non-adherence 32 33 ; lack of expertise in mental health professionals to interpret physical health results 34 37 ; workload issues 32 33 38 ; staff reluctant to see MS screening as their responsibility. 32–34 Authors across studies identified the following facilitators: investment of staff in physical health monitoring 33 36 37 39 and staff flexibility by using alternative equipment and tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Has anyone else noticed that the epigram at the start of this paper 1 is incorrectly attributed? It does not express a Taoist idea, and is not the kind of thing Lao Tsu would have written.…”
Section: A Fishy Businessmentioning
confidence: 99%